DIFFERENCES OF STUDENTS??? GENDER ON WRITING ABILITY USING CREATIVE DIARY - Tenia Ramalia (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2020)
The aim of this study was to determine students??? gender differences on writing ability using creative diary. This research was conducted to find out whether students??? gender affects to their writing ability. The design used in this research was one group pretest and posttest. The population of this research is the first semester students of communication sciences class 1C Unis academic year 2017/2018 which consist of 47 students in one class. The data were collected from a project of making creative diary and were analyzed by using SPSS 25. The result of the research shows that there is a difference between female and male students on writing ability using creative diary. Female students still have a better score than male students after they are given a pretest and posttest. It is shown by the number of percentage in three categories. Based on the result, it can be concluded that there is a difference of writing ability between female and male student